Movimento “Põe no Rótulo”: Net-Ativismo e interações nas redes sociais digitais - Vieira , Kalyne de Souza (2016)
This research investigates the formation of the net-activist movement "Põe no Rótulo", which appeared in digital social networks in February 2014, in order to sensitize society to the need for clear and precise information on allergenic ingredients on food labels. The study aims to understand how the interactions among subjects, technologies, territories and digital networks produced this net-activist action. The hypothesis of the research is that new communication and information technologies have produced an atmosphere able to approach and connect humans and nonhumans around common issues, promoting and stimulating actions that tensions the status quo. To understand this ambience, we chose the theoretical framework that recognizes the net-activism in the context of action and networked interaction. Thus, we seek support in Actor-Network Theory, in Connective Action, in Cosmopolitics, in Political Ecology, in Politician Transfiguration, as well as in the Networking, Ecology, Science Network Complexity, Social Networks and Digital Social Networks concepts. The study investigates the movement "Põe no Rótulo" interactions on the action's fanpage on Facebook, from February 2014 to June 2015. We conclude that movement "Põe no Rótulo" reveals the power of feeling and acting together, energized by networked digital materiality.